(untitled) (Politeja, 2015)
Political parties and party system of Ukraine: problems of formation in the conditions of state building and social transition Political parties are known to play a profound role in the formation and functioning of the political system of a state. In the countries that are experiencing social transformations their place and role are a bit different from those they hold in the countries with a developed democracy. Since independence proclamation (1991) Ukraine has been in a state of public transition: from the Soviet totalitarianism with a communist single-party to a liberal pluralism. However, this way is rather complicated and ambiguous. The process of social transformation in Ukraine is complicated by the fact that it takes place simultaneously with the process of state building and setting the stages of sovereign statehood. The aim of this study is to analyze the peculiarities of political parties and party system establishment in Ukraine under the conditions of social transformation and state building.